PENGARUH BIAYA PRODUKSI DAN KUALITAS PRODUK TERHADAP PENETAPAN HARGA JUAL YANG KOMPETITIF PADA UMKM AYAM GEPREK KA 88 - Yanti Gultom; Dwita Agustina Rumahorbo; Tessalonika Sianipar; Hamonangan Siallagan (Komunitas Manajemen Kompetitif, 2026)
This study was conducted to determine and measure the extent to which production costs and product quality influence competitive selling prices for the Ayam Geprek KA 88 business. Competition in the culinary sector is currently intense, especially in areas surrounding campuses in Medan. In such situations, companies must take steps to determine selling prices that not only increase profitability but also attract consumer interest in a growing market. The study uses an associative quantitative approach to explain the relationships between variables. Data were collected through observation, interviews, and questionnaires distributed to 35 respondents. The collected data were then processed using multiple linear regression analysis, a t-test to test partial effects, and the coefficient of determination (R²) using SPSS. The results indicate that production costs have a significant influence on selling prices. This is evidenced by a t-value of 3.219 and a significance level of 0.003, lower than the conventional threshold of 0.05. Similarly, product quality was also found to have a significant impactshown to have a significant influence, with a t-value of 5.206 and a significance level of 0.000. Simultaneously, these two variables also significantly influence selling price determination, as indicated by the F-value of 32.912 with a significance level of 0.000. The coefficient of determination (R²) of 0.673 indicates that these two variables explain 67.3% of the variation in selling price determination, with the remainder explained by other factors not examined in this study. Based on the findings of this study, it is recommended that businesses manage production costs more efficiently without sacrificing product quality. This way, they can set optimal selling prices and maintain strong competitiveness in the market.